TINGKAT PARTISIPASI KELUARGA BERENCANA PASCA OTONOMI DAERAH DI KOTA MAGELANG (Hasil Analisis Data KB dan KS Tahun 2012) - , ANISATUN NURUL ALAM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Imposed regional autonomy in Indonesia since January 2001 brought widespread influence in various fields ranging from government, finance, to public service. Issuance of Law no.22, 1999 led to the government district/municipality has the power enormous political economy and in the same time period the central government's power is significantly reduced. Similarly, the policy reproductive health, at first under the BKKBN still be at the central position. But since June 2003, BKKBN submitted to the District/City. Family Planning Program is a program that is recognized as an effective population program to reduce fertility. In line with this, the development of facilities and infrastructure health and family planning services should always be a priority. Family planning after the implementation of regional autonomy, which is not only seen from the acceptor and young couple participation but also participation of BKKBN both in terms of costs incurred for family planning programs. Autonomous regions, particularly in the field of Family Planning provides many influences, among others : the first addressed the central BKKBN now handled by the District/City respectively . As in Magelang, BKKBN policy first set directly by the central budget from start up to the need of contraception. But after autonomy, the need for contraception and shipping each district that filed so tailored to the needs of each district. The positive impact of this policy is no need for contraceptives and other wasted. Participation of acceptors for the city of Magelang to conduct its family planning can be seen from the increase in new planning participants and the increasing number of active participants family planning programs each month. New planning participants more likely to use government services because many are young couple and a new partner during pregnancy had children who went to the village midwife. Participants Family Planning more active use of family planning services for the comfort and ease of private consultations to be an alternative option and many of those who work so much easier family planning after hours in the afternoon or evening. Lack of control of the local government in supporting the family planning program control is felt greatly affect the performance of BKKBN, so the main BKKBN field officers or field officers should be able to play an active role by providing information to health centers, hospitals, family planning clinics, and into the villages through âdasawismaâ. Basically contraceptive needs in the city of Magelang in each district have been met either in the form of pills, syringes, condoms, IUDs and Implants. Even for vasectomy and tubectomy also served for free. Thorough understanding of the body and reproductive health of the participants KB can affect the choices of contraceptives was wearing. With satisfaction and stability so the use of contraceptives will increase the sustainability of contraceptive use, so will provide a better demographic impact.